qPCR-based quantification reveals high plant host-specificity of endophytic colonization levels in leaves - de Paula, Caio César Pires; Bárta, Jiří; Borovec, Jakub; Frouz, Jan; Rychtecký, Pavel; Sirová, Dagmara (American journal of botany, 2025)
PREMISE: Despite the high functional importance of endophytes, we still have limited understanding of the biotic and abiotic factors that influence colonization of plant hosts along major ecological gradients and lack quantitative estimates of their colonization extent. In this study, we hypothesized that the developmental stage of the ecosystem will affect the levels of bacterial and fungal endophytic assemblages in the foliar endosphere. METHODS: We quantified levels of bacterial and fungal endophytes in leaves of four plant hosts at four stages of vegetation succession using an optimized qPCR protocol with bacteria-specific 16S and fungi-targeting primers. RESULTS: (1) The ecosystem developmental stage did not have a significant effect on the colonization levels of bacterial or fungal endophytes. (2) Colonization levels by bacterial and fungal endophytes were governed by different mechanisms. (3) Endophytic colonization levels and their relationship to foliar tissue stoichiometry were highly host specific. CONCLUSIONS: Quantifying colonization levels is important in the study of endophytic ecology, and the fast, relatively low-cost qPCR-based method can supply useful ecological information, which can significantly enhance the interpretation potential of descriptive data generated, for example, by next-generation sequencing.
Keywords: listy rostlin; Fungi; kvantitativní polymerázová řetězová reakce; Ecosystem; fungi‐bacteria ratios; endofyty; cell counts; Bacteria; houby; qPCR; soil chronosequence; Real-Time Polymerase Chain Reaction; hostitelská specificita; foliar endophyte; Plant Leaves; ekosystém; ecological succession; Host Specificity; Endophytes